2021
DOI: 10.1007/s11356-021-13628-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous monitoring of SARS-CoV-2, bacteria, and fungi in indoor air of hospital: a study on Hajar Hospital in Shahrekord, Iran

Abstract: The novel SARS-CoV-2 outbreak was declared as pandemic by the World Health Organization (WHO) on March 11, 2020. Understanding the airborne route of SARS-CoV-2 transmission is essential for infection prevention and control. In this study, a total of 107 indoor air samples (45 SARS-CoV-2, 62 bacteria, and fungi) were collected from different wards of the Hajar Hospital in Shahrekord, Iran. Simultaneously, bacterial and fungal samples were also collected from the ambient air of hospital yard. Overall, 6 positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
1
19
0
2
Order By: Relevance
“…In indoor environments, most of the research efforts have been focused on measuring airborne viral particle concentrations in hospitals, intensive care units, and quarantine areas showing that concentrations could be higher compared to outdoor (Borges et al 2021;Chia et al 2020;Ge et al 2020;Hu et al 2020;Jin et al 2020;Lednicky et al 2020;Liu et al 2020;Razzini et al 2020;Santarpia et al 2020;Passos et al 2021;Vosoughi et al 2021). However, other studies reported no detectable airborne viral RNA even in proximity of COVID-19 patients (Cheng et al 2020;Faridi et al 2020;Ong et al 2020;Dumont-Leblond et al 2021;Hemati et al 2021). This underlines that there are difficulties in comparison of results obtained in different studies for several reasons: (i) the strength of the source (number of infected individuals); (ii) the absence of a standard measurement protocol (Borges et al 2021;Pan et al 2019;Robotto et al 2021); (iii) the influence of specific mitigation strategies; (iv) the role of mechanical ventilation in the different indoors environments and the size of the rooms.…”
Section: Introductionmentioning
confidence: 99%
“…In indoor environments, most of the research efforts have been focused on measuring airborne viral particle concentrations in hospitals, intensive care units, and quarantine areas showing that concentrations could be higher compared to outdoor (Borges et al 2021;Chia et al 2020;Ge et al 2020;Hu et al 2020;Jin et al 2020;Lednicky et al 2020;Liu et al 2020;Razzini et al 2020;Santarpia et al 2020;Passos et al 2021;Vosoughi et al 2021). However, other studies reported no detectable airborne viral RNA even in proximity of COVID-19 patients (Cheng et al 2020;Faridi et al 2020;Ong et al 2020;Dumont-Leblond et al 2021;Hemati et al 2021). This underlines that there are difficulties in comparison of results obtained in different studies for several reasons: (i) the strength of the source (number of infected individuals); (ii) the absence of a standard measurement protocol (Borges et al 2021;Pan et al 2019;Robotto et al 2021); (iii) the influence of specific mitigation strategies; (iv) the role of mechanical ventilation in the different indoors environments and the size of the rooms.…”
Section: Introductionmentioning
confidence: 99%
“…This study was performed on men with COVID-19 infection confirmed by an rRT-PCR from an oropharyngeal sample [ 10 ]. We recruited 70 fertile men who have had COVID-19 from August 2021 to December 2021 and have had children within the last two years.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, surveillance of virus-laden aerosols is suitable for monitoring this path and assessing qualitative and quantitative molecular epidemiological information on population exposure to SARS-CoV-2 ( Anand et al 2021 ). So far, many studies have detected the presence of SARS-CoV-2 RNA in indoor aerosols, mainly in hospitals ( Ang et al, 2022 , Baboli et al, 2021 , Barbieri et al, 2021 , Bazzazpour et al, 2021 , Cheng et al, 2020 , Chia et al, 2020 , Ding et al, 2021 , Dumont-Leblond et al, 2020 , Feng et al, 2021 , Ghaffari et al, 2021 , Guo et al, 2020 , Habibi et al, 2021 , Hemati et al, 2021 , Kenarkoohi et al, 2020 , Lednicky et al, 2020a , Lednicky et al, 2020b ; Liu et al, 2020 , Lopez et al, 2021 , Nor et al, 2021 , Passos et al, 2021 , Razzini et al, 2020 , Stern et al, 2021a , Stern et al, 2021b ; Tan et al, 2020 , Yarahmadi et al, 2021 , Zhou et al, 2021 ), as well as in residential rooms ( Nannu Shankar et al 2022 ), transportation ( Hadei et al, 2021 , Lednicky et al, 2021 , Moreno et al, 2021 ) and other public indoor places ( Hadei et al 2021 ). Some further detected the presence of SARS-CoV-2 nucleocapsids ( Krambrich et al 2021 ) or even viable viruses ( Lednicky et al, 2020a , Lednicky et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%